Construction of the Research Body on the Phenomenon of Business Incubation: Diversity of Paradigms and Attempts at Theorization (Global Journal of Management and Business Research, 2021)
The mainstream of research on incubators and incubation emerged with the presentation of the first results on the profiles of incubators by Temali and Campbell in 1984. Since that date, several contributors have advanced knowledge on the phenomenon of incubation. The construction of the research body was on the occasion of the creation of several research paradigms, which we will take care to detail and compare throughout this article. Ultimately, diversity concerns not only the paradigms and current research on this subject, but also the definitions and taxonomy of incubation structures.
Keywords: research paradigms; taxonomy; business incubator; entrepreneurial support